A análise crítica do discurso e as redes sociais: o caso da prisão do ex-presidente Lula - Santos, Raíssa Castro Camilo dos (2021)
Using critical discourse analysis, which observes and investigates the textual dimensions of discourse, this paper proposed to examine posts from homepages that are for and against the imprisonment of the former President of the Republic of Brazil, Luiz Inácio Lula da Silva, through critical discourse analysis. The discursive practice found in the posts and comments demonstrate political support and lack thereof. The material investigated within critical discourse analysis presents the political and social changes, while at the same time, showing the political passage of the period narrated by supporters and opponents of the Lula government. The focus of the study was based on renowned authors in the area who brought contributions so that the observation could be complete, pointing out hegemony, ideological and gender issues, Critical Discourse Analysis (Fairclouch, 2000) with social and linguistic approach in the relationship of power. Other contributions to this dissertation were from authors such as Ducrot (1987), Thompson (1995), for example. The research was qualitative and analytical, since the materials of analysis were sought in research on the internet and Facebook, and analytical, because the images of the posts were protagonists and played an important role in contributing to this analysis by proposing the message of non-verbal language or even the arts and photos chosen to print them. It is possible to conclude that this work demonstrates that critical discourse analysis contributes to the understanding of how society, oppositions, and discourses are composed of history, power, social practice, hegemony, and partisanship, among other aspects. This dissertation is important for the historical and political understanding of this period, moreover, it seeks to translate through theory and Critical Discourse Analysis the power of social media posts, of what a message intrinsically carries with partiality.